Genrens tøven - Sestoft, Carsten (K&K - Kultur og Klasse, 2007)
Romanens status i det 17. århundredes Frankrig The hesitations of a genre: The status of the novel in seventeenth-century France In answering the question: What was the novel in seventeenth-century France? – this article provides insight into some important points of the early history of the genre. The contradiction between its non-existence in official (Aristotelian) poetics and its existence as a popular commodity on the book market was, in the course of the seventeenth century, reconciled in the emergent category of belles lettres as a plurality of genres mainly defined by their public of honnêtes gens, while attempts at legitimizing the novel as belonging to such Aristotelian genres as epic or history generally failed; and at the end of the century a number of convergences – between epic and novel, between the designations roman and nouvelle, and between the ‘high’ and ‘low’ forms of the novel – seem to point to the fact that the social existence of the genre had been strengthened, even if it was the English novel of the eighteenth century that could be said to reap the profits of this stronger position. Using historical semantics and cultural sociology to study the status of the novel in seventeenth-century France thus leads to a clearer understanding of the specificity of the novel as a literary and cultural genre.